2020
DOI: 10.5194/acp-2020-962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating Upper Silesian coal mine methane emissions from airborne in situ observations and dispersion modeling

Abstract: Abstract. Abundant mining and industrial activities located in the Upper Silesian Coal Basin (USCB) lead to large emissions of the potent greenhouse gas (GHG) methane (CH4). The strong localization of CH4 emitters (mostly confined to known coal mine ventilation shafts) and the large emissions of 448/720 kt CH4 yr−1 reported in the European Pollutant Release and Transfer Register (E-PRTR 2017) and the Emissions Database for Global Atmospheric Research (EDGAR v4.3.2) make the USCB a prime research target for val… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
2
8
0
Order By: Relevance
“…In our precursor study (Luther et al, 2019), we used stop-and-go measurements of the column-average dry-air mole fractions of CH 4 (XCH 4 ) by a mobile, ground-based Fourier Transform Spectrometer (FTS) to evaluate the mining emissions of individual ventilation facilities, and found similar emissions as suggested by the E-PRTR inventory. The total USCB emission estimates of Fiehn et al (2020) and Kostinek et al (2020), based on airborne in situ measurements, are in broad agreement with the E-PRTR data for single flights. Using airborne imager data, Krautwurst et al (2021) found some discrepancies between their estimates and the E-PRTR inventory for small groups of ventilation facilities.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…In our precursor study (Luther et al, 2019), we used stop-and-go measurements of the column-average dry-air mole fractions of CH 4 (XCH 4 ) by a mobile, ground-based Fourier Transform Spectrometer (FTS) to evaluate the mining emissions of individual ventilation facilities, and found similar emissions as suggested by the E-PRTR inventory. The total USCB emission estimates of Fiehn et al (2020) and Kostinek et al (2020), based on airborne in situ measurements, are in broad agreement with the E-PRTR data for single flights. Using airborne imager data, Krautwurst et al (2021) found some discrepancies between their estimates and the E-PRTR inventory for small groups of ventilation facilities.…”
Section: Introductionsupporting
confidence: 79%
“…Our simulations of methane dispersion in the USCB partition into two steps largely adopting the basic setup reported by Kostinek et al (2020): first (Sect. 3.1), the wind fields are modeled by a two domain WRF setup including assimilation of the wind lidar observations.…”
Section: Dispersion Modeling Of Methanementioning
confidence: 99%
See 1 more Smart Citation
“…Whenever sunlight is needed to perform the measurement, less turbulent conditions, for example in the morning after sunrise or winter, should be preferred. Further, it should be pointed out that, with a lidar, cross-sectional plume measurements can also be performed over water bodies whose detrimental reflective properties often impede the use of passive remote sensing (Gerilowski et al, 2015;Krautwurst et al, 2021;Larsen and Stamnes, 2006). Therefore, plumes from offshore installations can also be addressed with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…The CoMet campaign saw the deployment of a suite of airborne instruments to measure atmospheric CH 4 and CO 2 , alongside a variety of ground-based instruments. In particular, the synergetic use of active remote sensing (lidar) (Amediek et al, 2017;Wildmann et al, 2020), passive spectrometry (Krautwurst et al, 2021;Luther et al, 2019), and in situ measurements (Fiehn et al, 2020;Gałkowski et al, 2021;Kostinek et al, 2020) supported by modeling activities (Chen et al, 2020;, as well as the validation of existing (e.g., Sentinel-5P, GOSAT, Greenhouse gases Observing SATellite) and the preparation of upcoming (e.g., MERLIN, MEthane Remote sensing Lidar missioN) GHG satellite missions, was aimed at.…”
Section: Introductionmentioning
confidence: 99%